Investigating Speaking Ability Through Intrapersonal Intelligence On Efl Learners: A Systematic Literature Review - Al Hazimi, Naseef Efriza; Heryatun , Yayu; Perdana , Purnama Rika; Marjuni, Marjuni (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This Study aim to investigate the speaking ability and intrapersonal intelligence in recent years. This research uses a systematic literature review. The search for relevant articles through the Pubmed, Eric, and JSTOR databases with keywords speaking ability and intrapersonal intelligence was carried out by the research team. Based on the result, Pubmed found 78 articles, Eric found 110 articles, and JSTOR found 101 articles. Furthermore, based on the criteria: speaking, speaking comprehension, multiple intelligence and intrapersonal intelligence, articles were selected. The researcher found that Implementing Learner-Centered Activities: Shifting from the traditional teacher-centered approach to learner-centered activities can empower students to take ownership of their learning process. By engaging students in activities that activate their multiple intelligences, educators can improve their speaking skills. Pair and Group Work: Encouraging collaborative activities such as pair or group work can help activate multiple intelligences in students. By engaging in interactive tasks, students can develop their speaking skills while honing their intrapersonal intelligences